GROWTH AND YIELD RESPONSE OF RED CHILLIES ON THE APPLICATION OF DOLOMIT LIME AND LIQUID ORGANIC FERTILIZER IN PEAT SOIL - Peter _; Maulidi _; Agus Hariyanti (Jurnal Sains Pertanian Equator, 2019)
This study aims to obtain the best interaction between dolomite lime and dose of liquid organic fertilizer on the growth and yield of red chili on peat soil. The research was carried out in the experimental garden of the Faculty of Agriculture, Tanjungpura University, from July to September 2018. This study used a field experimental method in factorial formula with a Completely Randomized Design (CRD) consisting of two factors i.e. dolomite lime and liquid organic fertilizer. Dolomite lime factor consists of 3 treatment levels, which were 210 g dolomite lime / polybag, 277 g dolomite lime / polybag, and 343 g dolomite lime / polybag, and liquid organic fertilizer factor consisting of 3 treatment levels, 1 ml / liter of water, 2 ml / liter of water, and 3 ml / liter of water, each treatment were repeated 3 times. The observed variables were plant height (cm), plant dry weight (g), leaf chlorophyll content (spad unit), root volume (cm3), fruit weight per fruit (g), fruit weight per plant (g), and number of fruit per plant (fruit). The results showed that none of dolomite lime dose have interaction with dose of liquid organic fertilizer on peat soil was found, but the effective dose was able to increase the growth and yield of chili by the application of 210 g dolomite lime and 1 ml / liter of liquid organic fertilizer.Keywords : red chili, peat, dolomite lime, liquid organic fertilizer